Headspace solid-phase microextraction and gas chromatography/ion trap-mass spectrometry applied to a living system: Pieris brassicae fed with kale - Fernandes, F. (2011)
The influence of Pieris brassicae feeding on kale was monitored, by evaluating its effect on the volatiles released by the plant through time. This is the first study applying headspace solid-phase microextraction (HS-SPME) and gas chromatography/ion trap-mass spectrometry to an isolated insect, as most studies analyse the insect–plant system as a whole, being unable to evaluate the contribution of the insect itself. Substantial differences were noticed between the volatiles composition of kale before and after the insect’s attack. More than 60 compounds were found, including terpenes, lipoxygenase pathway by-products, ketones, norisoprenoids, etc. After insect attack, l-camphor, sabinene and a-thujene were found and limonene and eucalyptol suffered a noticeable increase. A considerable rise in (Z)-3-hexenyl acetate was also observed. In vivo accumulation of limonene and camphor by the insect was detected. The findings contribute to the knowledge of the ecological interactions between the two species.